2014
DOI: 10.1186/1472-6831-14-78
|View full text |Cite
|
Sign up to set email alerts
|

The potential oral health impact of cost barriers to dental care: findings from a Canadian population-based study

Abstract: BackgroundPrior to the 2007/09 Canadian Health Measures Survey, there was no nationally representative clinical data on the oral health of Canadians experiencing cost barriers to dental care. The aim of this study was to determine the oral health status and dental treatment needs of Canadians reporting cost barriers to dental care.MethodsA secondary data analysis of the 2007/09 Canadian Health Measures Survey was undertaken using a sample of 5,586 Canadians aged 6 to 79. Chi square tests were conducted to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 28 publications
15
42
0
2
Order By: Relevance
“…It is well known that dental insurance is a strong predictor of access to dental care and therefore reduces the prevalence and severity of dental diseases. 40,41 Thus, increasing the awareness of oral health disparities in the pediatric SDB population is a necessary prerequisite to improving the oral health of this population. There are some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that dental insurance is a strong predictor of access to dental care and therefore reduces the prevalence and severity of dental diseases. 40,41 Thus, increasing the awareness of oral health disparities in the pediatric SDB population is a necessary prerequisite to improving the oral health of this population. There are some limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, though, our study identified income-related differences for opioid use only among those who reported a toothache in the past month (that is, no real income effect exists for prescription opioid use in the absence of a toothache). Given that those from lower socioeconomic backgrounds disproportionately suffer from untreated dental needs [5657], our findings suggest that policies designed to improve access to dental services for those who are most socially and economically marginalized may, in part, assuage the need for opioid analgesics among those in BC by either preventing, or directly treating, the cause of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Forgoing dental care is associated with poorer oral health [ 28 – 32 ]. A very recent study published in this Journal showed that Canadians from the general adult population who reported cost barriers to dental care had more untreated decay, missing teeth, poorer oral health and more frequent oral pain [ 30 ]. Those reporting cost barriers also had a higher prevalence of needing dental treatment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%